Cardiac Magnetic Resonance–Measured Left Atrial Volume and Function and Incident Atrial Fibrillation: Results From MESA (Multi-Ethnic Study of Atherosclerosis). (August 2016) - Habibi, Mohammadali; Samiei, Sanaz; Ambale Venkatesh, Bharath; Opdahl, Anders; Helle-Valle, Thomas M.; Zareian, Mytra; Almeida, Andre L.C.; Choi, Eui-Young; Wu, Colin; Alonso, Alvaro; Heckbert, Susan R.; Bluemke, David A.; et al.
Abstract : Background—: Early detection of structural changes in left atrium (LA) before atrial fibrillation (AF) development could be helpful in identification of those at higher risk for AF. Using cardiac magnetic resonance imaging, we examined the association of LA volume and function, and incident AF in a multiethnic population free of clinical cardiovascular diseases. Methods and Results—: In a case–cohort study embedded in MESA (Multi-Ethnic Study of Atherosclerosis), baseline LA size and function assessed by cardiac magnetic resonance feature-tracking were compared between 197 participants with incident AF and 322 participants randomly selected from the whole MESA cohort. Participants were followed up for 8 years. Incident AF cases had a larger LA volume and decreased passive, active, and total LA emptying fractions and peak global LA longitudinal strain (peak LA strain) at baseline. In multivariable analysis, elevated LA maximum volume index (hazard ratio, 1.38 per SD; 95% confidence interval, 1.01–1.89) and decreased peak LA strain (hazard ratio, 0.68 per SD; 95% confidence interval, 0.48–0.96), and passive and total LA emptying fractions (hazard ratio for passive LA emptying fractions, 0.55 per SD; 95% confidence interval, 0.40–0.75 and hazard ratio for active LA emptying fractions, 0.70 per SD; 95% confidence interval, 0.52–0.95), but not active LA emptying fraction, were associated with incident AF. Conclusions—: Elevated LA volumes and decreased passive and total LA emptying fractions were independently associated with incident AF in an asymptomatic multiethnic population. Including LA functional variables along with other risk factors of AF may help to better risk stratify individuals at risk of AF development. Abstract : Supplemental Digital Content is available in the text.